INTRODUCTION OF AGRICULTURAL GREEN TOURISM IN FARMS AS ONE OF THE DIRECTIONS OF EFFECTIVE USE THEIR RESOURCE POTENTIAL - Ivaniv , S. I.; Drabchuk , N. Yu. (The actual problems of regional economy development, 2020)
The article is devoted to the possibility of obtaining additional income by farms through the introduction of rural green tourism. The aim of the study is to study the features of the introduction of rural green tourism in farms in Ukraine, in particular the features, benefits and constraints of development. The following methods were used in the study: graphic to reflect the development of agritourism in OTG; abstract-logical to define the essence of the concept of "rural green tourism" and "agrocluster"; analysis - for the formation of the peculiarities of the development of rural green tourism in Ukraine; grouping to identify the main factors that slow down the development of agritourism in Ukrainian villages; generalization, which was used to draw conclusions from the study. The article substantiates the importance of additional activities by farmers in the form of agritourism and reflects the main advantages of such activities. The restraining factors that take place in the development of agritourism activities in Ukraine are studied. An analysis of the development of rural green tourism in foreign countries. The directions of agrotourism development in OTG are singled out. The influence of the cluster system on the economic situation of rural areas and the reasons for slow development are described. The scientific novelty of the study is the formation of the authors of a structured sequence of actions in the implementation of additional activities in the form of agritourism; formation of the definition of "agrocluster". The results obtained in the research process can be used by farms, agricultural enterprises, personal farms to implement agritourism activities in their region.